Clinical and neurophysiological matching in patients of different age with lumbar spine stenosis - Lidiya Chebotariova; Albina Tretiakova; Yuriy Pedachenko; Elena Krasilenko (Ukrainian Neurosurgical Journal, 2012)
Introduction. The urgency of a subject is caused by need to optimize diagnostics in patients of different age with lumbar spine stenosis.Materials and methods. The results of clinical and neurophysiological (NPh) examination of 79 patients aged from 17 to 80 years with lumbar spine stenosis were analyzed. Depending on age patients were divided into 5 groups. Clinical signs and NPh-markers of roots and spinal structures defeat were studied. NPh examination included: electroneuromyography (ENMG) with F-waves registration, evoked motor potentials (EMP) recording. For identification of clinical and NPh changes we carried out provocative tests and loading test: walking to an symptoms aggravation.Results. In all patients with lumbar spine stenosis EМP changes were revealed in comparison with those in control group: latency of cortical EMP was increased in 41 (51.9%) patients, time of central motor conduction — in 33 (41.8%). The frequency of NPh spinal defeats in patients from 3–5 groups was authentically higher than in patients from 1st and 2nd  groups. Accompanying sensomotor polyneuropathy at lumbar spine stenosis according to ENMG data was revealed in the 3rd group at 14.3% patients, in the 4th group — at 32.2%, in the 5th group — at 80%.Conclusions. It was established that in patients with lumbar spine stenosis with age frequency of poliradicular and myelopathy symptoms, caudo- and myelogenic intermittent claudication increases.